Traditional tutorial system - fit for purpose or past its sell by date? University students’ experiences - Davids, Mogamat Noor (South African Journal of Higher Education, 2016)
Universities in South Africa as well as elsewhere have seen a significant increase in student enrolment resulting in large class sizes. Consequently the potentially detrimental effects of large classes on student learning have become a permanent feature that needs constant monitoring. An increase in student enrolment numbers is often not accompanied by a proportionate increase in teaching staff and resources. Therefore an increase in student numbers without increase in teaching staff arguably compromises the quality of teaching and learning. The tutorial system is a known teaching strategy employed to minimize negative consequences of large classes. In the post-apartheid era concern have been expressed about the effectiveness of the tutorial system The context of this paper is a compulsory B.Ed module ‘The History of Education’ at a higher education institution. In the 2013 academic year, 820 students had to be accommodated in a tutorial system of 27 groups taught by 12 tutors. The projection for 2014 is 1100 students divided amongst 44 tutorials of 25 students each. This paper is concerned with the pedagogical value of the tutorial system viewed from the perspective of students. The paper’s focus is therefore the experiences of students as participants in a tutorial system as a supplementary teaching strategy. Data were extracted from quantitative sections of the student course evaluation forms (N=60) and a qualitative questionnaire (N=50) conducted with a random sample of students. Excel spread sheet and content analysis were employed to analyse the data sets. Using Shulman’s Pedagogical content knowledge (PCK) and Wenger’s concept ‘community of practice’ (COP) as conceptual framework, the findings reveal arbitrary, contradictory and unequal participatory learning outcomes. Given the diminishing ‘fit for purpose’ between learning objectives and outcomes, recommendations are made to make tutorials meaningful and productive in the immediate future